Comparison of the Effectiveness of Assertiveness Training and Logotherapy on Cognitive Emotional Regulation and Psychological Well-Being in Mothers of Children with Autism Spectrum Disorder - Barnameh, Narges; Bagheri, Nasrin; Tanha, Zahra (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present research aimed to compare the effectiveness of assertiveness training and Logotherapy on cognitive emotional regulation and psychological well-being in mothers of children with autism spectrum disorders.Methods: The research design was a quasi-experimental pre-test post-test with a control group. The study population included all mothers of children with autism spectrum disorders in Tehran during the years 2022-2023. Sixty eligible individuals were randomly sampled into three groups: Experimental Group 1, Experimental Group 2, and a Control Group. The research variables were measured using the Gratz and Roemer (2004) Emotion Regulation Questionnaire and the Ryff (1989) Psychological Well-being Scale. Experimental Groups 1 and 2 received eight 2-hour sessions of Logotherapy and assertiveness training respectively, while the control group received no intervention during this period. Data analysis was conducted using SPSS software.Findings: The results indicated that there was a significant difference in the effectiveness of assertiveness training and Logotherapy on cognitive emotional regulation among mothers of children with autism spectrum disorder (p = 0.05). There was also a significant difference in the effectiveness of assertiveness training and Logotherapy on the psychological well-being of these mothers (p = 0.05).Conclusion: Therefore, it can be concluded that both assertiveness training and Logotherapy enhance cognitive emotional regulation, with Logotherapy being a more effective method for increasing psychological well-being compared to assertiveness training.